Enhancement of Heat Transfer in The Tube-Sid of A Double Pipe Heat Exchanger by Wire Coils - Slaiman, Qasim J. M.; Znad, Abbas N. (Nahrain University College of Engineering Journal, 2017)
Heat transfer enhancement by wire coils is adopted in order to increase the thermal performance of a double pipe heat exchanger. The heat exchanger adopted is 1245 mm effective length, 28 mm outer diameter and changeable inner diameter (11 or 14 mm). Wire coils of e = 1 mm and p = 10, 20, 30 and 40 mm are used as turbulence promoters to augment heart transfer inside the inner tube at a Reynolds number range of 5000 to 40000. Water is used as the working fluid in the two sides. Variation in the experimental conditions is attained by changing the mass flowrates of unenhanced side and changing the inlet temperature of hot fluid. These conditions are followed in order to have as large amount of data points as possible in addition to observe the effect of changing these conditions. Heat transfer is increased inside the inner tube by 2.43 folds, as compared to empty tube at the same Reynolds number accompanied by friction factor increase of 4.75 folds. New correlations of Nusselt number and friction factor for the enhanced tubes are proposed as functions of Reynolds number, Prandtl number and the geometrical characteristics of inserts and tube sizes.